(untitled) (University Journal of Zoology, Rajshahi University, 2008)
The present study assessed the semen characteristics of bulls used for Artificial Insemination (AI) programme in Bangladesh with regard to season, ambient temperature and relative humidity. A total of 3720 semen samples from 71 bulls were collected from Central Cattle Breeding Station and Dairy Farm (CCBSDF), Savar, Dhaka, Rajshahi Dairy and Cattle Improvement Farm (RDCIF), Rajabarihat, Rajshahi and District Artificial Insemination Centre (DAIC), Rajshahi during 1995 - 2002. Semen was collected by artificial vaginal method once a week. Different seasons viz. spring, summer, autumn and winter had significant effect (P<0.05) on colour, density, mass activity, sperm concentration, sperm motility, total sperm cells/ejaculate, total number of motile sperm cells/ejaculate, number of semen doses per collection and postfreezing motility of sperm. The maximum values of these semen characteristics were found in summer. Ambient temperature groups of <21°C, 21-25°C, 25- 29°C and >29°C had significant (P<0.05) effect on all the semen characteristics except for volume of semen. The highest volume of semen was found at >29°C and the lowest at 25-29°C. The total number of sperm cells/ejaculate, total number of motile sperm cells/ejaculate and number of semen doses per collection were found in >29 °C temperature groups. Relative humidity groups of <65%, 65-75%, 75-85% and >85% had significant effect on all the semen characteristics excluding for volume of semen and number of semen doses per collection. The largest volume of semen, colour, mass activity, total sperm cells/ejaculate, total motile sperm cells/ejaculate and number of semen doses/collection were found in >85% relative humidity and the smallest in 65%-75% relative humidity. Finally, this study recommended that, summer season, ambient temperature groups of >29°C and Relative humidity groups of >85% are suitable for excellent semen characteristics. Key words: AI bulls; semen characteristics; season; temperature; relative humidity Univ. j. zool. Rajshahi Univ. Vol. 26, 2007. pp. 81-88